Biochemical identification of endophytic bacteria isolates from medicinal plant kayu jawa lannea coromandelica (houtt.) merr - Eka Astuty; Indas Wari Rahman; Melda Yunita (JPBIO (Jurnal Pendidikan Biologi), 2023)
Medicinal plants and their endophytes are a source of valuable bioactive compounds and their secondary metabolites which contribute to more than 80% of natural medicines available in the market. A plant that has long been used as a traditional medicinal herb for healing is the Kayu Jawa (Lannea coromandelica (Houtt) Merr). This study aimed to characterization and identification of endophytic bacterial isolates isolated from medicinal plants Kayu Jawa (L. coromandelica (Houtt.) Merr). This research is a laboratory experimental research. In total, 8 isolates were selected as representatives of the bacterial community living in the tissues of Kayu Jawa (L. coromandelica (Houtt.) Merr). The microscopic observation was performed by Gram staining. Biochemical identification was conducted using Vitek 2. The results showed that Bacillus was the dominant genus in this study followed by Staphylococcus and Pantoea. Based on the research that has been done, it can be concluded that the endophytic bacteria isolated from Kayu Jawa Lannea coromandelica (Houtt) Merr, six isolates belonging to Bacillus and another two belonging to Staphylococcus and Pantoea genera. However, for the exploration of this prospective application, it is very important to do a systematic study of the biological and distribution of endophytic bacteria in the host.